The Role of Nuclear Diplomacy - S. Sriwidjaja (Atom Indonesia, 2007)
In the midst of nuclear countries and non-nuclear countries in the framework of non-proliferation and disarmament, Indonesia has played an important role. Indonesia has been actively involved in each activity at the international level to create a world free from nuclear weapons. This involvements needs to be maintained and increased in the years to come. As a large country, Indonesia should play a key role in the field of nuclear diplomacy. All of the efforts of nuclear diplomacy as mentioned above had a clear objective to support Indonesia’s energy program, at the institution framework as well as capacity building. Indonesia’s effort is also directed to attain appropriated international public acceptance.